#TITLE_ALTERNATIVE# - HADI MAHMUDI (NIM 13205115), M.
Any electric power supply system must be able to serve all requirements on demand at all times. The difference between the amount of base load and peak load period causes the generation of running the operation uneconomical. Therefore, pumped storage power plant technology is possible to apply. Pumped storage power plant can store energy at base load period to be reused during peak load period. In this final project, presented an approach method for calculating the optimal installed capacity of pumped storage power plant. This method allows one to calculate the optimal installed capacity of pumped storage power plant for each curve using the system load curve duration with graphical approach in modeling the load curve. In this final project, the method is applied to the daily load curve of Jawa-Bali and it regions. For the load curve of Jawa-Bali obtained the optimal value of pumped storage power plant capacity of 2,250 MW with a base load capacity of 14,404 MW. In a further analysis, described about pumped storage power plant application to the load curve and calculation of it margin based on the electricity basic tariff of PLN. From the calculation, applied pumped storage power plant can make the total margin will reach amount 1.028 billion per day.